Post-combustion slipstream CO2-capture test facility at Jiangyou Power Plant, Sichuan, China: facility design and validation using 30% wt monoethanolamine (MEA) testing. Issue 2 (19th March 2020) - Wang, Baodeng; Cui, Qian; Zhang, Guoping; Long, Yinhua; Sun, Yongwei; Zhao, Xinglei; He, Zhendong; Ku, Anthony Y
Abstract: Given the dominant share of coal in China's energy-generation mix and the fact that >50% of the power plants in the country are currently <15 years old, efforts to significantly reduce China's CO2 footprint will require the deployment of CO2 capture across at least part of its fleet of coal-fired power plants. CO2 -capture technology is reaching commercial maturity, but it is still necessary to adapt the technology to regional conditions, such as power-plant design and flexible operation in the China context. Slipstream facilities provide valuable field data to support the commercialization of CO2 capture. We have built a slipstream facility at Jiangyou power plant in Sichuan that will allow us to explore China-relevant issues, especially flexible operation, over the next few years. We plan to share our results with the broader CO2 -capture and CO2 -storage (CCS) community to accelerate the deployment of CCS in China. This paper describes the design of the slipstream facility and presents results from our steady-state qualification tests using a well-studied benchmark solvent: 30% wt monoethanolamine (MEA). The results from our MEA tests compare favorably to results reported from other slipstream-test facilities around the world, allowing us to commission our system and establish a reference baseline for future studies. Abstract : CO2 capture technology is reaching commercial maturity, but it is still necessary to adapt the technology to regional conditions. A slipstream carbon-capture facility recently built at Jiangyou power plant in Sichuan will allow exploration of China-relevant issues, especially flexible operation. Graphical Abstract: